Acute myeloid leukemia following a primary mediastinal germ cell tumor - Huimin Hong; Yan Su; Chenghao Chen; Lejian He; Shuai Zhu; Wei Lin; Mei Jin; Xisi Wang; Ruidong Zhang; Huyong Zheng; Qi Zeng; Xiaoli Ma (Wiley, 2020)
Abstract Introduction There is a known association between primary mediastinal germ cell tumor (PMGCT) and hematologic malignancy that is not linked to treatment. They are exceptionally rare entities with a low morbidity and a poor prognosis. Case presentation An 11‐year‐old boy presented with an anterior mediastinal mass diagnosed as a malignant germ cell tumor on the basis of an excisional biopsy. He was found to have acute myeloid leukemia (AML) two years after the chemotherapy for his germ cell tumor. The clinical course was very aggressive with a survival time of only 1 week after diagnosis of AML associated with PMGCT. Conclusion AML associated with PMGCT needs to be diagnosed correctly. Relevant examinations should be carried out in patients with PMGCTs during and after chemotherapy, and long‐term follow‐up is still necessary to reduce the risk of morbidity and mortality.